Assessing Institutional Quality Assurance Effectiveness through Internal Quality Audit Results - Syukrul Hamdi; Lia Yuliana; Riki Perdana; Nirmala Adhi Yoga Pambayun; Martutik Martutik; Sri Maharini (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2026)
This mixed-methods study, employing correlation analysis, investigated the impact of the internal quality assurance (IQA) system at a leading university in Indonesia. Drawing on data from Internal Quality Audits (AMI) conducted across eleven faculties and institutional units, the research aimed to evaluate institutional performance and identify areas for enhancement. Using a four-point rating scale, descriptive analysis revealed the highest mean scores in Mission (3.86), Governance and Leadership (3.86), Education (3.82), and Finance, Facilities, and Technology (3.77). These findings indicate institutional strengths in strategic direction, organizational performance management, and resource sustainability. Analysis at the faculty level revealed notable variations. For instance, overachievement was observed in specific units (e.g., FBSB, FIPP) and particular selection criteria (e.g., FISHIPOL – Teaching), while the PPGPPI Directorate achieved maximum scores across all indicators. Conversely, lower mean scores were recorded for Community Service (3.58) and Tri Dharma Outputs (3.41), both rated "Very Good," suggesting potential shortcomings in external engagement and research impact. Pearson bivariate correlation analysis identified two primary clusters of significant positive correlations: one among strategic, governance, financial, and output indicators (r = 0.887–0.944; p < 0.01), and another among supporting academic dimensions. The study contributes empirically grounded insights to inform quality policy development. It recommends implementing benchmarking of best practices to enhance community engagement and establishing continuous professional development programs for faculty to strengthen overall institutional quality.